2004
DOI: 10.1103/physrevb.69.174507
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an incommensurate magnetic resonance inLa2xSrxCuO

Abstract: We study the effect of a magnetic field (applied along the c-axis) on the low-energy, incommensurate magnetic fluctuations in superconducting La1.82Sr0.18CuO4. The incommensurate peaks at 9 meV, which in zero-field were previously shown to sharpen in q on cooling below Tc [T. E. Mason et al., Phys. Rev. Lett. 77, 1604], are found to broaden in q when a field of 10 T is applied. The applied field also causes scattered intensity to shift into the spin gap. We point out that the response at 9 meV, though occurri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
97
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(107 citation statements)
references
References 81 publications
8
97
2
Order By: Relevance
“…Instead, the field moves spectral weight into the spin gap. The study on x = 0.18 indicated that the increase in weight in the gap is accompanied by a decrease in the intensity peak above the gap [51], the latter result being comparable to the effect seen in YBa 2 Cu 3 O 6.6 [50]. For x = 0.163, an enhancement of the incommensurate scattering was observed below 10 K forhω = 2.5 meV.…”
Section: Magnetic Fieldsupporting
confidence: 58%
See 1 more Smart Citation
“…Instead, the field moves spectral weight into the spin gap. The study on x = 0.18 indicated that the increase in weight in the gap is accompanied by a decrease in the intensity peak above the gap [51], the latter result being comparable to the effect seen in YBa 2 Cu 3 O 6.6 [50]. For x = 0.163, an enhancement of the incommensurate scattering was observed below 10 K forhω = 2.5 meV.…”
Section: Magnetic Fieldsupporting
confidence: 58%
“…For an intermediate doping concentration of x = 0.144, Khaykovich et al [230] have recently shown that, although no elastic magnetic peaks are seen at zero field, a static SDW does appear for H > H c ∼ 3 T. Such behavior [224], [223], [230], [52], and [51]. The solid curve suggests the shape of a boundary between a state with spin-density-wave order and superconductivity on the left and superconductivity alone on the right, as first proposed by Demler et al [225].…”
Section: Magnetic Fieldmentioning
confidence: 99%
“…2; the small-and large-spin-gap results demonstrate, respectively, the existence of an incommensurate [34] or a commensurate [33] resonance mode.…”
Section: Figmentioning
confidence: 99%
“…Also, in both systems the suppression of SC by a high magnetic field results in a zero-temperature insulator-to-metal transition upon doping [24,25]. Even though the pairing symmetry is different in the cuprates [26][27][28] and the FeSCs [29-32], a resonant spin excitation, characterized by wave vectors around those of the magnetic order in the parent compound, exists in the SC state of both systems [33][34][35].…”
mentioning
confidence: 99%
See 1 more Smart Citation